Giiwe: An Indigenous-led Model for Inter-organizational Homelessness Prevention - Sanchez-Pimienta, Carlos Ernesto; Giroux, Diane; Masuda, Jeff (The International Indigenous Policy Journal)

(untitled) (Scholarship@Western (Western University), 2024)
Preventing people from experiencing homelessness is a complex task requiring the coordination of multiple actors. There are various frameworks for homelessness prevention; however, there is no published example of an Indigenous-led model. We present the Giiwe model for systems homelessness prevention led by M’Wikwedong Indigenous Friendship Centre in Owen Sound, Canada. Giiwe hosts regular in-person meetings that use ceremony, Indigenous Knowledges, discussion, and follow-up actions to increase service access among a network of over 20 organizations. Building on Giiwe’s experience, we discuss how Western and Indigenous worldviews impact inter-organizational collaboration. Giiwe’s success suggests funding and policy contexts mandating partnerships between Indigenous and non-Indigenous organizations could benefit from ceding space for initiatives affirming Indigenous collaboration approaches.